Cattlemen's Day 2022, Beef Cattle Research (Kansas Agricultural Experiment Station Research Reports, 2022)
This report includes research on beef cattle management, reproduction, nutrition, and meat science conducted at Kansas State University.
Keywords: beef cattle management; reproduction; nutrition; meat science; prescribed burning; grazing